Development and testing of a module to promote generic oral contraceptive prescribing among nurse practitioners. Issue 1 (January 2020) - Chee, Mark; Lenti, Gena; Farnan, Jeanne; Cook, Michelle; Weissman, Arlene; Wallingford, September; Moriates, Christopher; Shah, Neel; Lynch, Shalini; Stebbins, Marilyn; Ngooi, Samantha; Norenberg, Allison; et al.
Abstract : ABSTRACT: Although generic oral contraceptives (OCPs) can improve adherence and reduce health care expenditures, use of generic OCPs remains low, and the factors that affect generic prescribing are not well understood. We aimed to understand the barriers and facilitators of generic OCP prescribing and potential solutions to increase generic OCP prescribing, as well as pilot an educational module to address clinician misconceptions about generic OCPs. We developed focus group scripts using the 4D model of appreciative inquiry. A total of four focus groups occurred, two at the American Association of Nurse Practitioners (AANP) national conference and two at the American College of Physicians (ACP) Internal Medicine meeting. Focus group transcripts were analyzed using a constant comparative method with no a priori hypothesis to generate emerging and reoccurring themes. Findings from these focus groups were used to develop an educational module promoting generic OCP prescribing. Participants were recruited from the AANP Network for Research and the ACP Research Panel. This study demonstrates that health system factors, workflow factors, clinician factors, and patient factors were the main barriers to and facilitators of generic OCP prescribing. Nurse practitioners were responsive to an educational module and reported increased willingness to discuss and prescribe generic OCPs after completing the module. Interventions to increase generic OCP prescribing must address clinician and patient factors within the context of workflow and larger health system factors.